2021
DOI: 10.31234/osf.io/xebwm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personality Psychology

Abstract: Personality psychology, which seeks to study individual differences in thoughts, feelings, and behaviors that persist over time and place, has experienced a renaissance in the last few decades. It has also not been reviewed as a field in the Annual Review since 2001 (Funder, 2001). In this chapter, we seek to provide an update, while also providing a meta-organizational structure to the field. In particular, personality psychology has a prescribed set of four responsibilities that it implicitly or explicitly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 165 publications
(195 reference statements)
0
2
0
Order By: Relevance
“…The life span perspective conceptualizes aging as a lifelong process of development and adaptation (Baltes et al, 2006). Research embedded in this perspective has found personality traits to be subject to change across the entire life span (Costa et al, 2019;Graham et al, 2020;Specht, 2017;Specht et al, 2014; for recent reviews, see Bleidorn et al, 2021;Roberts & Yoon, 2021). Although a majority of personality development takes place in adolescence and emerging adulthood (Bleidorn & Schwaba, 2017;Pusch et al, 2019;, personality traits also change in middle and older adulthood (e.g., Allemand et al, 2008;Damian et al, 2019;Kandler et al, 2015;Lucas & Donnellan, 2011;Mõttus et al, 2012;S.…”
Section: Personality Development In Middle and Older Adulthoodmentioning
confidence: 99%
“…The life span perspective conceptualizes aging as a lifelong process of development and adaptation (Baltes et al, 2006). Research embedded in this perspective has found personality traits to be subject to change across the entire life span (Costa et al, 2019;Graham et al, 2020;Specht, 2017;Specht et al, 2014; for recent reviews, see Bleidorn et al, 2021;Roberts & Yoon, 2021). Although a majority of personality development takes place in adolescence and emerging adulthood (Bleidorn & Schwaba, 2017;Pusch et al, 2019;, personality traits also change in middle and older adulthood (e.g., Allemand et al, 2008;Damian et al, 2019;Kandler et al, 2015;Lucas & Donnellan, 2011;Mõttus et al, 2012;S.…”
Section: Personality Development In Middle and Older Adulthoodmentioning
confidence: 99%
“…Personality traits are defined as characteristic and automatic patterns of thinking, feeling, and behaving that are consistent over time and across situations (Roberts & Yoon, 2021). They represent cognitive, affective, and behavioural tendencies, averaged across situations (Fleeson & Jayawickreme, 2015).…”
Section: Introductionmentioning
confidence: 99%